The Influence of Organizational Culture and Compensation on Employee Performance with Job Satisfaction as an Intervening Variable (Employee Case Study at PT. Saida Indica Pratama) - M. Dahsya Karesna; Fadhilah Izhari; Nur Aeni; Hasanah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to determine: (1) The influence of organizational culture on job satisfaction, (2) The influence of compensation on job satisfaction, (3) The influence of organizational culture on employee performance, (4) The influence of compensation on employee performance, (5) The influence Job Satisfaction on Employee Performance, (6) The Influence of Organizational Culture by Intervening Job Satisfaction on Employee Performance, (7) The Effect of Compensation by Intervening Job Satisfaction on Employee Performance. The data analysis model used is path analysis with associative quantitative research methods, namely a population of 100 and a sample of 80. The research results show that (1) Organizational culture has a significant effect on job satisfaction, (2) Compensation has a significant effect on job satisfaction, ( 3) Organizational culture has a significant effect on employee performance, (4) Compensation has an insignificant effect on employee performance, (5) Job satisfaction has a significant effect on employee performance, (6) Organizational culture with intervening job satisfaction has a significant effect on employee performance, (7) Compensation by intervening job satisfaction has a significant effect on employee performance.